Conhecimentos locais e a cadeia produtiva do goiamum (Cardisoma guanhumi, Lattreille, 1825) no litoral paraibano - Takahashi, Mauricio Avelar (2008)
The Cardisoma guanhumi, is a natural resource within many others in the mangrove ecosystem that has been suffering with the habitat degradation, mainly by pollution and habitats retraction, and its commercial exploitation. For many years this resources has been a way of subsistence and income, therefore men of this communities have been accumulating knowledge on the biology, ecology and methods of capturing this animal. This study aimed to describe the local knowledge, some aspects of such techniques and its commercialization in restaurants in the littoral of the State of Paraíba, Brazil. Semistructured questionnaires, open dialogues and interviews were conducted with 10 gatherers and 8 intermediaries pointed out by community members (snow ball technique) in the municipalities of João Pessoa, Bayeux, Santa Rita and Rio Tinto. Among those 4 gatherers were observed separately in a routine day of work where photographic records were made and audios-visual where possible as allowed by them. The identification of the productive chain was made in two different ways, first from gatherers information, whom pointed the destination of their products, and second by owners of bars indicating the origin of their products. We interviewed 5 owners of bars, with semi-structured questionnaires, in order to obtain information about the trade of the blue landcrab or goiamum (as known in Brazil), and their market values. The biometrics values of the carapace width were obtained with a 1mm precision packmeter for specimens already caught and on commercialization process. The data from the questionnaires and biometrics values of the carapace width were confronted with the current legislation. The local gatherers knowledge’s about the biology, ecology and capture the goiamum was rich in information and innovations. They showed whether holders knowledge accurate when compared to the scientific literature. The results show that in the productive chain the low demand of this resource when compared with the others crustaceans like crabs (Ucides cordatus), shrimps, lobsters, and others genders of “fishes”, is a positive mark to the sustainability of its activity, however the unselective demand for sex is a negative mark. Although the recent law protection during reproductive period, this resource has been affected by the over fishing and habitats retraction, caused mainly by sugar cane cultures, cot and urbanization, seriously compromising the survey of this species, and consequently affecting the life of those who depend of its commercialization. The low market value has been dragging this resource to over fishing, and consequently the gatherers have been breaking the law for essential family income. Therefore are urgently needed educational projects and alternatives income activity projects to changes the social patterns of the gatherers. At the same time the stipulation of regard periods on the activity during the reproductive period of the species, likely happens to lobster among other fishing resources, is needed to protect the perpetuation of this species.